Treatment of mouse cumulus‐oocyte complexes with L‐carnitine during vitrification and in vitro maturation affects maturation and embryonic developmental rate after parthenogenetic activation. (23rd October 2021) - Zare, Zohreh; Rezaei, Noorollah; Mohammadi, Moslem
Abstract: The technique of oocyte vitrification remains a challenge in most animal species. The present study aimed to evaluate the effects of cumulus cell presence and L‐carnitine (LC) treatment during vitrification of selected immature oocytes by brilliant cresyl blue (BCB) staining on maturation and embryonic developmental rate after parthenogenetic activation. Immature oocytes were obtained from C57BL/6 female mice ovaries and stained with BCB. The BCB + cumulus‐oocyte complexes (COCs) were then selected and random parts of COCs were denuded from cumulus cells (denuded oocytes: DOs). COCs and DOs were treated with/out LC (0.6 mg/ml) during vitrification and in vitro maturation (IVM) procedures. A number of non‐vitrified COCs were also treated with LC during the IVM process (fresh group). Maturation rate, intracellular glutathione (GSH) contents, and developmental competence of oocytes were also examined. The GSH levels in vitrified DOs+LC and vitrified COCs+LC groups were significantly higher ( p < 0.01) than untreated vitrified‐warmed COCs and DOs. Maturation rate and blastocyst developmental rate were reduced after the vitrification‐warming procedure compared with the fresh group. The vitrified COCs+LC group showed a higher percentage of mature oocytes and the ability to develop to blastocyst stage than the vitrified‐warmed DOs group ( p < 0.01). These data indicated that the presence of cumulus cells around the competent oocyte and LC treatment during vitrification and IVM procedure could improve parthenogenetic developmental competence of vitrified‐warmed oocytes by increasing GSH levels and accelerating oocyte maturation.